VD_FINDINFO HC / 2024 / 770 vom 9. Oktober 2024 - VD Tribunal cantonal (2024)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, FARDEAU DE LA PREUVE | 8 CC, 337c al. 3 CO, 152 al. 1 CPC (CH), 180 CPC, 311 al. 1 CPC (CH)